Organosilicon detachable heat-conducting adhesive and preparation method thereof
By controlling the proportion of components in the silicone thermal bonding adhesive and selecting suitable reactants, a high thermal conductivity and removable bonding adhesive is achieved, which solves the problem of long curing time and inability to disassemble in the prior art, and improves the Resource utilization efficiency in new energy vehicles and other fields.
Patent Information
- Application Number
- CN202411658599.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-07
AI Technical Summary
The existing silicone thermal bonding glue takes more than 60 minutes to cure at high temperature and cannot be disassembled, resulting in the problem of waste of resources in new energy vehicles and other fields.
Using the silicone removable thermal bonding adhesive mixed with components A and B at a 1:1 mass ratio, select suitable coupling agents and expandable by controlling the ratio and crosslinking density of vinyl silicone oil to hydrogen-containing silicone oil. Microspheres, using highly efficient catalysts and inhibitors, achieve fast curing and removable properties in low temperatures.
The bonding adhesive with a thermal conductivity up to 4W/mK, Al-Al bonding shear strength of 3.0 to 4.0MPa, and elongation of break of 25 to 50%, was achieved, and was quickly cured under 110℃@10min, passing through hot air The gun is heated at 160-260℃, and the disassembly can be completed in 60-120 seconds to avoid wasting resources.
Smart Images

Figure BDA0005142703750000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal conductive interface materials and adhesive materials, and specifically to a removable silicone thermal conductive adhesive and a preparation method thereof. The removable silicone thermal conductive adhesive can be used in the fields of consumer electronics, semiconductors, communications and new energy vehicles. The removable silicone thermal conductive adhesive has the characteristics of high thermal conductivity, high adhesion, low temperature rapid curing and detachability. Background Art
[0002] The current silicone thermal conductive adhesives on the market generally have a thermal conductivity of 0.5 to 3 W / m·K, and an Al-Al bonding shear strength of 1.8 to 3.5 MPa. It takes more than 60 minutes to cure at 125°C, and the adhesive cannot be disassembled and repaired after operation. At present, silicone thermal conductive adhesives have been widely used in the field of new energy vehicles. If the thermal conductive adhesive cannot be disassembled, when one of the bonded units is damaged, all the bonding units must be replaced together, which will cause a huge waste of resources. Therefore, there is an urgent need for a detachable silicone thermal conductive adhesive. Summary of the invention
[0003] In view of the above deficiencies in the prior art, an object of the present invention is to provide a removable silicone thermally conductive adhesive and a preparation method thereof.
[0004] To achieve the above objectives, the technical solutions adopted are:
[0005] One of the purposes of the present invention is to provide a removable silicone thermal conductive adhesive, comprising a component A and a component B, wherein the mass ratio of the component A to the component B is 1:1; by mass fraction, the component A comprises 4 to 6% of vinyl silicone oil, 0.2 to 0.5% of a coupling agent, 0.1 to 1.5% of a dispersant, 0.3 to 0.4% of a catalyst, 88 to 94% of an alumina filler, and 1 to 3.6% of expandable microspheres; the component B comprises 4 to 6% of vinyl silicone oil, 0.2 to 0.5% of a coupling agent, 0.1 to 1.5% of a dispersant, 0.01 to 0.05% of an inhibitor, 0.8 to 1.2% of hydrogenated silicone oil, 88 to 94% of an alumina filler, and 1 to 3.6% of expandable microspheres.
[0006] Preferably, the vinyl silicone oil is a vinyl-terminated silicone oil or a mixture thereof having a viscosity of 250 to 5000 cps and a vinyl content of 0.06 to 0.22 mmoles / g.
[0007] Preferably, the hydrogen-containing silicone oil is at least one of terminal hydrogen-containing silicone oil, side hydrogen-containing silicone oil, and terminal-side hydrogen-containing silicone oil having a viscosity of 30 to 500 cps and a hydrogen content of 2.4 to 8.4 mmoles / g.
[0008] More preferably, the molar ratio of the hydrogen-containing silicone oil to the vinyl silicone oil is 1.5 to 4:1.
[0009] Preferably, the expandable microspheres have an initial expansion temperature of 160-260° C., a particle size of 15-50 μm, and an expansion ratio of 400-1000%.
[0010] Preferably, the coupling agent is at least one of vinyltrimethoxysilane, an oligomer of vinyltrimethoxysilane, vinyltriethoxysilane, an oligomer of vinyltriethoxysilane, methylvinyldimethoxysilane, an oligomer of methylvinyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, an oligomer of vinyltri(2-methoxyethoxy)silane, vinyltriisopropoxysilane, and an oligomer of vinyltriisopropoxysilane.
[0011] Preferably, the dispersant is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and 2-methoxypolyoxyethylenepropyltrimethoxysilane.
[0012] Preferably, the catalyst is a platinum catalyst having a platinum content of 2000 to 5000 ppm.
[0013] Preferably, the inhibitor is at least one of ethynyl cyclohexanol, methyl butynol, and 3,7,11-trimethyl dodecyn-3-ol.
[0014] The second object of the present invention is to provide a method for preparing the removable thermally conductive silicone adhesive, comprising the following steps:
[0015] (1) Preparation of component A: 4-6% by mass of vinyl silicone oil, 0.2-0.5% of coupling agent, 0.1-1.5% of dispersant, 0.3-0.4% of catalyst, 88-94% of alumina filler, and 1-3.6% of expandable microspheres are mixed, and stirred in an oil bath at 20-30° C. for 2-5 hours at a rotation speed of 10-25R;
[0016] (2) preparing component B: mixing 4-6% by mass of vinyl silicone oil, 0.2-0.5% of coupling agent, 0.1-1.5% of dispersant, 0.01-0.05% of inhibitor, 0.8-1.2% of hydrogenated silicone oil, 88-94% of alumina filler, and 1-3.6% of expandable microspheres, and stirring in an oil bath at 20-30° C. for 2-5 h at a rotation speed of 10-25R;
[0017] (3) Mixing: Component A and component B are mixed in a mass ratio of 1:1 to obtain the above-mentioned silicone detachable thermal conductive adhesive.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The organosilicon detachable thermally conductive adhesive described in the present invention controls the elongation at break and the bonding shear strength of the thermally conductive adhesive by controlling the ratio and crosslinking density of vinyl (-CH=CH2) and hydrogen-containing (-H) groups in vinyl silicone oil and hydrogen-containing silicone oil; enhances the bonding shear strength of the adhesive by selecting a suitable coupling agent to react with thermally conductive powder and expandable microspheres and controlling the degree of reaction; selects expandable microspheres with suitable expansion temperature, particle size and expansion ratio, and adjusts the thermally conductive adhesive to a suitable elongation at break and hardness, so as to avoid the thermally conductive adhesive having too low elongation or too high hardness after curing, which causes the expandable microspheres to be locked inside the colloid and unable to expand when heated for disassembly, thereby causing disassembly failure; and adjusts the curing temperature and time by selecting an efficient catalyst and controlling the ratio of the catalyst to the inhibitor. The thermally conductive adhesive can be cured quickly at low temperature, and after the curing operation, it can be externally heated. Within a certain temperature range, the expandable microspheres can expand rapidly, greatly weakening the interfacial bonding force, so that it can be disassembled for repair. The thermal conductivity of the thermally conductive adhesive can reach up to 4W / mK, the Al-Al bonding shear strength can reach 3.0-4.0MPa, the elongation at break is 25-50%, and it can be quickly cured at 110℃@10min. The disassembly can be completed by setting the hot air gun to 160-260℃ and blowing for 60-120s. DETAILED DESCRIPTION
[0020] The present invention is described below in conjunction with examples, which are only used to explain the present invention and are not used to limit the scope of the present invention.
[0021] Example 1
[0022] Step 1. Component A: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.3% of a platinum catalyst with a platinum content of 2000ppm, 94% of alumina filler, 1% of expandable microspheres with an initial expansion temperature of 160°C, a particle size of 15μm, and an expansion ratio of 400%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0023] Step 2. Component B: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.01% of ethynylcyclohexanol, 0.8% of end-side hydrogenated silicone oil with a viscosity of 30cps and a hydrogen content of 8.4mmoles / g, 93% of alumina filler, 1.49% of expandable microspheres with an initial expansion temperature of 160°C, a particle size of 15μm, and an expansion ratio of 400%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0024] Step 3. Mix component A and component B in a mass ratio of 1:1 to obtain the silicone detachable thermally conductive adhesive.
[0025] Example 2
[0026] Step 1. Component A: 6% of terminal vinyl silicone oil with a viscosity of 5000cps and a vinyl content of 0.06mmoles / g, 0.5% of vinyltriethoxysilane, 1.5% of γ-glycidyloxypropyltrimethoxysilane, 0.4% of a platinum catalyst with a platinum content of 5000ppm, 88% of alumina filler, 3.6% of expandable microspheres with an initial expansion temperature of 260°C, a particle size of 50μm, and an expansion ratio of 1000%, stirred in an oil bath at 30°C for 5h at a speed of 25R.
[0027] Step 2. Component B: 6% of terminal vinyl silicone oil with a viscosity of 5000cps and a vinyl content of 0.06mmoles / g, 0.5% of methylvinyldimethoxysilane, 1.5% of hexadecyltrimethoxysilane, 0.05% of 3,7,11-trimethyldodecyl-3-ol, 1.2% of a mixture of terminal hydrogenated silicone oil and side hydrogenated silicone oil with a viscosity of 500cps and a hydrogen content of 2.4mmoles / g, the mass ratio of terminal hydrogenated silicone oil to side hydrogenated silicone oil is 5:3, 88% of alumina filler, 2.75% of expandable microspheres with an initial expansion temperature of 260°C, a particle size of 50μm, and an expansion ratio of 1000%, stirred in an oil bath at 30°C for 5h at a speed of 25R.
[0028] Step 3. Mix component A and component B in a mass ratio of 1:1 to obtain the silicone detachable thermally conductive adhesive.
[0029] Example 3
[0030] Step 1. Component A: 4% of terminal vinyl silicone oil with a viscosity of 1000cps and a vinyl content of 0.12mmoles / g, 0.5% of vinyltri(2-methoxyethoxy)silane, 0.1% of hexadecyltrimethoxysilane, 0.4% of a platinum catalyst with a platinum content of 5000ppm, 92% of an alumina filler, 2% of expandable microspheres with an initial expansion temperature of 180°C, a particle size of 20μm, and an expansion ratio of 1000%, stirred in an oil bath at 25°C for 3h at a rotation speed of 15R.
[0031] Step 2. Component B: 4% of a mixture of terminal vinyl silicone oils with a viscosity of 1000cps and a vinyl content of 0.12mmoles / g, 0.5% of vinyl tri(2-methoxyethoxy)silane, 0.1% of hexadecyltrimethoxysilane, 0.01% of methylbutynol, 1.01% of a mixture of terminal hydrogenated silicone oil and side hydrogenated silicone oil with a viscosity of 50cps and a hydrogen content of 3.8mmoles / g, the mass ratio of terminal hydrogenated silicone oil to side hydrogenated silicone oil being 5:2, 92% of alumina filler, 2.38% of expandable microspheres with an initial expansion temperature of 180°C, a particle size of 20μm, and an expansion ratio of 1000%, stirred in an oil bath at 25°C for 3h at a speed of 15R.
[0032] Step 3. Mix component A and component B in a mass ratio of 1:1 to obtain the silicone detachable thermally conductive adhesive.
[0033] Comparative Example 1
[0034] Step 1. Component A: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.3% of a platinum catalyst with a platinum content of 2000ppm, 94% of alumina filler, 1% of expandable microspheres with an initial expansion temperature of 160°C, a particle size of 15μm, and an expansion ratio of 400%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0035] Step 2. Component B: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.01% of ethynylcyclohexanol, 0.8% of terminal hydrogenated silicone oil with a viscosity of 30cps and a hydrogen content of 2.4mmoles / g, 93% of alumina filler, 1.49% of expandable microspheres with an initial expansion temperature of 160°C, a particle size of 15μm, and an expansion ratio of 400%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0036] Step 3. Mix component A and component B in a mass ratio of 1:1 to obtain the silicone detachable thermally conductive adhesive.
[0037] Comparative Example 2
[0038] Step 1. Component A: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of neoalkoxy tri(dioctyl pyrophosphate) titanate, 0.5% of hexadecyltrimethoxysilane, 0.3% of a platinum catalyst with a platinum content of 2000ppm, 94% of alumina filler, 1% of expandable microspheres with an initial expansion temperature of 160°C, a particle size of 15μm, and an expansion ratio of 400%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0039] Step 2. Component B: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.01% of ethynylcyclohexanol, 0.8% of end-side hydrogenated silicone oil with a viscosity of 30cps and a hydrogen content of 8.4mmoles / g, 93% of alumina filler, 1.49% of expandable microspheres with an initial expansion temperature of 160°C, a particle size of 15μm, and an expansion ratio of 400%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0040] Step 3. Mix component A and component B in a mass ratio of 1:1 to obtain the silicone detachable thermally conductive adhesive.
[0041] Comparative Example 3
[0042] Step 1. Component A: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.3% of a platinum catalyst with a platinum content of 2000ppm, 94% of alumina filler, 1% of expandable microspheres with an initial expansion temperature of 160°C, a particle size of 15μm, and an expansion ratio of 400%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0043] Step 2. Component B: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.01% of ethynylcyclohexanol, 0.8% of terminal hydrogenated silicone oil with a viscosity of 30cps and a hydrogen content of 8.4mmoles / g, 94.49% of alumina filler, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0044] Step 3. Mix component A and component B in a mass ratio of 1:1 to obtain the silicone detachable thermally conductive adhesive.
[0045] Comparative Example 4
[0046] Step 1. Component A: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.3% of a platinum catalyst with a platinum content of 2000ppm, 94% of alumina filler, 1% of expandable microspheres with an initial expansion temperature of 160°C, a particle size of 15μm, and an expansion ratio of 400%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0047] Step 2. Component B: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.01% of ethynylcyclohexanol, 0.8% of terminal hydrogenated silicone oil with a viscosity of 30cps and a hydrogen content of 8.4mmoles / g, 93% of alumina filler, 1.49% of expandable microspheres with an initial expansion temperature of 200°C, a particle size of 2μm, and an expansion ratio of 100%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0048] Step 3. Mix component A and component B in a mass ratio of 1:1 to obtain the silicone detachable thermally conductive adhesive.
[0049] Comparative Example 5
[0050] Step 1. Component A: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.3% of a platinum catalyst with a platinum content of 200ppm, 94% of alumina filler, 1% of expandable microspheres with an initial expansion temperature of 160°C, a particle size of 15μm, and an expansion ratio of 400%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0051] Step 2. Component B: 4% by mass of terminal vinyl silicone oil with a viscosity of 250cps and a vinyl content of 0.22mmoles / g, 0.2% of vinyltrimethoxysilane, 0.5% of dodecyltrimethoxysilane, 0.01% of ethynylcyclohexanol, 0.8% of end-side hydrogenated silicone oil with a viscosity of 30cps and a hydrogen content of 8.4mmoles / g, 93% of alumina filler, 1.49% of expandable microspheres with an initial expansion temperature of 160°C, a particle size of 15μm, and an expansion ratio of 400%, stirred in an oil bath at 20°C for 2h at a speed of 10R.
[0052] Step 3. Mix component A and component B in a mass ratio of 1:1 to obtain the silicone detachable thermally conductive adhesive.
[0053] The organic silicone detachable thermally conductive adhesive obtained in each embodiment and comparative example was tested as shown in Table 1, and the results are shown in Table 1.
[0054] Table 1. Performance results of the removable thermally conductive silicone adhesives of the embodiments and comparative examples
[0055]
[0056] It can be seen from the above data that the performance of the comparative examples is lower than that of the organosilicon detachable adhesive of the present invention. In comparative example 1, the ratio of vinyl (-CH=CH2) in the vinyl silicone oil to hydrogen-containing (-H) groups in the hydrogen-containing silicone oil is too high, and the crosslinking density is insufficient, resulting in reduced shear strength; the coupling agent used in comparative example 2 has no vinyl functional group, and a large amount of powder filling cannot react with the resin matrix, which will reduce the shear strength; comparative example 3 has no expandable microspheres, and the shear strength does not decrease after high-temperature purging, and does not have detachable performance; the expansion ratio and particle size of the expandable microspheres in comparative example 4 are too small, and the expanded volume is small after heating and cannot reduce the shear strength; comparative example 5 has too little catalyst and cannot be completely cured at a lower temperature; and the organosilicon detachable adhesive described in the present invention, after high-temperature purging, the expandable microspheres expand rapidly, reducing the contact area of the bonding interface, and the bonding shear strength decreases rapidly to reach a detachable level.
[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A removable silicone thermally conductive adhesive, characterized in that: The invention comprises a component A and a component B, wherein the mass ratio of the component A to the component B is 1:1; in terms of mass fraction, the component A comprises 4-6% of vinyl silicone oil, 0.2-0.5% of a coupling agent, 0.1-1.5% of a dispersant, 0.3-0.4% of a catalyst, 88-94% of an alumina filler, and 1-3.6% of expandable microspheres; the component B comprises 4-6% of vinyl silicone oil, 0.2-0.5% of a coupling agent, 0.1-1.5% of a dispersant, 0.01-0.05% of an inhibitor, 0.8-1.2% of hydrogenated silicone oil, 88-94% of an alumina filler, and 1-3.6% of expandable microspheres.
2. The removable thermally conductive silicone adhesive according to claim 1, characterized in that: The vinyl silicone oil is a vinyl-terminated silicone oil or a mixture thereof with a viscosity of 250 to 5000 cps and a vinyl content of 0.06 to 0.22 mmoles / g.
3. The removable thermally conductive silicone adhesive according to claim 2, characterized in that: The hydrogen-containing silicone oil is at least one of end hydrogen-containing silicone oil, side hydrogen-containing silicone oil, and end-side hydrogen-containing silicone oil, with a viscosity of 30 to 500 cps and a hydrogen content of 2.4 to 8.4 mmoles / g.
4. The removable thermally conductive silicone adhesive according to claim 1, characterized in that: The molar ratio of the hydrogen-containing silicone oil to the vinyl silicone oil is 1.5 to 4:
1.
5. The removable thermally conductive silicone adhesive according to claim 1, characterized in that: The expandable microspheres have an initial expansion temperature of 160-260° C., a particle size of 15-50 μm, and an expansion ratio of 400-1000%.
6. The removable thermally conductive silicone adhesive according to claim 1, characterized in that: The coupling agent is at least one of vinyltrimethoxysilane, an oligomer of vinyltrimethoxysilane, vinyltriethoxysilane, an oligomer of vinyltriethoxysilane, methylvinyldimethoxysilane, an oligomer of methylvinyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, an oligomer of vinyltri(2-methoxyethoxy)silane, vinyltriisopropoxysilane, and an oligomer of vinyltriisopropoxysilane.
7. The removable thermally conductive silicone adhesive according to claim 1, characterized in that: The dispersant is at least one of dodecyl trimethoxy silane, hexadecyl trimethoxy silane, γ-glycidyloxypropyl trimethoxy silane, and 2-methoxypolyoxyethylene propyl trimethoxy silane.
8. The removable thermally conductive silicone adhesive according to claim 1, characterized in that: The catalyst is a platinum catalyst with a platinum content of 2000 to 5000 ppm.
9. The removable thermally conductive silicone adhesive according to claim 1, characterized in that: The inhibitor is at least one of ethynyl cyclohexanol, methyl butynol, and 3,7,11-trimethyl dodecyn-3-ol.
10. A method for preparing the removable thermally conductive silicone adhesive as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Preparation of component A: 4-6% by mass of vinyl silicone oil, 0.2-0.5% of coupling agent, 0.1-1.5% of dispersant, 0.3-0.4% of catalyst, 88-94% of alumina filler, and 1-3.6% of expandable microspheres are mixed, and stirred in an oil bath at 20-30° C. for 2-5 hours at a rotation speed of 10-25R; (2) preparing component B: mixing 4-6% by mass of vinyl silicone oil, 0.2-0.5% of coupling agent, 0.1-1.5% of dispersant, 0.01-0.05% of inhibitor, 0.8-1.2% of hydrogenated silicone oil, 88-94% of alumina filler, and 1-3.6% of expandable microspheres, and stirring in an oil bath at 20-30° C. for 2-5 h at a rotation speed of 10-25R; (3) Mixing: Component A and component B are mixed in a mass ratio of 1:1 to obtain the above-mentioned silicone detachable thermal conductive adhesive.
Citation Information
Patent Citations
Thermal-spalling acrylic ester pressure-sensitive adhesive, adhesive tape and preparation method thereof
CN102559101A
High-thermal-conductivity low-viscosity two-component organic silicon pouring sealant and preparation method thereof
CN114032063A
Cited By
Heat-conducting foamed silica gel and preparation method thereof
CN120005403A